Local development in the context of SEZs under CPEC: Navigating pathways, trade-offs, and stakeholder perspectives in District Nowshera, KP, Pakistan - Akhtar, Farhan (Abdul Media Literasi, 2025)
This study examines the developmental role of newly established Special Economic Zones (SEZs) under the China-Pakistan Economic Corridor in District Nowshera, Khyber Pakhtunkhwa. It explores stakeholder perceptions, including those of entrepreneurs, business owners, development professionals, transport operators, officials, and community members, regarding economic, infrastructural, social, cultural, and environmental impacts of these initiatives. Guided by Social Exchange Theory, regression analysis was employed to examine the impact of five independent variables on local development. Results show that economic impact (β = 0.295, p < 0.01), infrastructure development (β = 0.318, p < 0.001), and socio-economic progress (β = 0.437, p < 0.001) significantly enhance perceptions of development, while cultural factors (β = −0.138, p = 0.025) and environmental sustainability (β = 0.219, p = 0.006) exert more subtle effects. A strong combined influence (β = 0.493, p < 0.001) affirms the multidimensional character of these dynamics. Respondents expressed optimism about job creation, connectivity, and economic opportunities, yet raised concerns about biodiversity loss, pollution, land conversion, and threats to local identity, norms, and traditions. These socio-cultural and environmental costs risk eroding support for SEZ-led development. The study concludes that sustainable local development requires policies that ensure equitable distribution of benefits, cultural sensitivity, and environmental safeguards, alongside programs for marginalised groups and long-term adaptive monitoring. Balancing economic objectives with social and ecological protections is essential for inclusive growth within the corridor framework.